Dinâmica populacional de cigarrinhas vetoras de xylella fastidiosa em citrus e métodos de avaliação de infectividade natural - Molina, Rúbia de Oliveira (2010)
The citrus crops develop an important role in the Brazilian economy, with an estimated production of 19,080,755 tons for 2010, especially as world's largest producer. However, the citrus crop is undermined by a disease known as citrus variegated chlorosis (CVC). This disease of citrus is caused by Xylella fastidiosa bacterial endophytes, rod-shaped, found in xylem vessels of plants. The dissemination occurs through insect vectors belonging to the Hemiptera order, Cicadellidae family, known as leafhoppers, which transmit the bacteria after feeding on infected plants. This study aimed to investigate the dynamics of the insect vector population, and the determination of an efficient protocol for DNA extraction, the leafhopper vectors to detect the bacteria through the technique of nested-PCR. The experiment was conducted in two commercial orchards of sweet orange (Citrus sinensis) varieties Pêra, Valência and Folha murcha, grafted on Rangpur lime (Citrus limonia), placed in Nova Esperança and Mandaguaçu cities, Paraná. To carry out the sampling was used yellow sticky traps, distributed in the peripheral and central plot, five rows were sampled in each plot. The traps were renewed in the orchard every thirty days during the evaluation period, from January 2008 to April 2010. In the study of behavior the main vector species captured were: Acrogonia citrina and Dilobopterus costalimai in Nova Esperança and Acrogonia citrina and Oncometopia facialis in Mandaguaçu. The results for DNA extraction from sharpshooter were best when used the phenol/chloroform. As the test nested-PCR was more efficient for the detection of bacteria.